2014
DOI: 10.1038/nutd.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Fatty fish consumption and risk of latent autoimmune diabetes in adults

Abstract: Objective:It has been suggested that intake of fatty fish may protect against both type 1 and type 2 diabetes. Hypotheses rest on the high marine omega-3 fatty acid eicosapentaenoic acid+docosahexaenoic acid (EPA+DHA) and vitamin D contents, with possible beneficial effects on immune function and glucose metabolism. Our aim was to investigate, for the first time, fatty fish consumption in relation to the risk of latent autoimmune diabetes in adults (LADA).Methods:Analyses were based on data from a Swedish case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…What triggers autoimmunity besides genetic factors is not clear; Psychological stress has been linked to type 1 diabetes in children (Rewers and Ludvigsson, 2016) but no such association was seen with LADA (Rasouli et al, 2017b). In line with some findings regarding type 1 diabetes in children (Stene et al, 2003; Norris et al, 2007; Niinistö et al, 2017), fatty fish is associated with a reduced risk of LADA but unrelated to type 2 diabetes in the ESTRID Study (Löfvenborg et al, 2014). A beneficial effect could hypothetically be attributed to omega 3-fatty acids which are abundant in fatty fish and possessing anti-inflammatory and immunomodulatory properties (Calder, 2013).…”
Section: Etiologysupporting
confidence: 84%
See 1 more Smart Citation
“…What triggers autoimmunity besides genetic factors is not clear; Psychological stress has been linked to type 1 diabetes in children (Rewers and Ludvigsson, 2016) but no such association was seen with LADA (Rasouli et al, 2017b). In line with some findings regarding type 1 diabetes in children (Stene et al, 2003; Norris et al, 2007; Niinistö et al, 2017), fatty fish is associated with a reduced risk of LADA but unrelated to type 2 diabetes in the ESTRID Study (Löfvenborg et al, 2014). A beneficial effect could hypothetically be attributed to omega 3-fatty acids which are abundant in fatty fish and possessing anti-inflammatory and immunomodulatory properties (Calder, 2013).…”
Section: Etiologysupporting
confidence: 84%
“…Results from ESTRID and HUNT studies. Estimates for low birth weight, sweetened beverages, coffee intake and fatty fish are based on data from the ESTRID Study (extracted from Löfvenborg et al, 2014, 2016; Hjort et al, 2015; Rasouli et al, 2018); estimates for BMI, smoking, physical activity and alcohol intake are based on pooled data from ESTRID and HUNT studies (extracted from Rasouli et al, 2013a,b, 2014, 2016; Hjort et al, 2018a,b); estimates for WHR is based on the HUNT Study (Hjort et al, 2018b).…”
Section: Etiologymentioning
confidence: 99%
“…The suggested positive association between artificially sweetened beverages and diabetes risk remains to be further explored. This study supports the notion that dietary factors may influence LADA development (21,40,41). This is important as the identification of modifiable risk factors could aid in preventing autoimmune diabetes.…”
Section: Discussionsupporting
confidence: 69%
“…Through these properties it has been demonstrated that n-3 PUFA supplementation may help in the prevention or treatment of many inflammatory-related diseases such as diabetes [4], [5], [6] and cardiovascular disease [7], [8], [9], [10], [11], [12], [13]. However, in recent years, the certainties of this assertion have been challenged by new discoveries [14], [15].…”
Section: Introductionmentioning
confidence: 99%